The Natural History of the Trans-Pecos : Desert Legends, Rugged Grandeur, and the Big Bend - Chapman, Brian R.; Bolen, Eric G. (Integrative natural history series., 2020)
"Complete with an introduction chronicling the stories of biologists and naturalists who have explored and defined the ecological areas of Texas over time, The Natural History of the Trans-Pecos explores the formation of the region more than 600 million years ago, the adaptability of its ecosystems, and the conservation efforts to keep these wildly diverse environments flourishing. Detailed descriptions, vivid anecdotes, and vibrant pictures of the features that make this region so unique emphasize the rugged grandeur of the Trans-Pecos"--